Urgent psychiatric consultations for suicide attempt and suicidal ideation before and after the COVID-19 pandemic in an Italian pediatric emergency setting - Apicella, Massimo; Serra, Giulia; Trasolini, Monia; Andracchio, Elisa; Chieppa, Fabrizia; Averna, Roberto; Iannoni, Maria Elena; Infranzi, Antonio; Moro, Marianna; Guidetti, Clotilde; Maglio, Gino; Raucci, Umberto; et al. (Frontiers in Psychiatry, 2023)
Suicidal attempts (SA) in youth have been increasing during last decades. We studied consultations, SA and Suicidal Ideation (SI) in a pediatric Emergency Department (ED). From January 1st, 2011, to May 31st, 2022, 606159 patients accessed the ED, 8397 of which had a Child Psychiatry Consultation (CPC). CPC increased significantly by 11-times in the last decade (155 in 2011 vs 1824 in 2021, p<0.001); CPC for SA increased significantly by 33-times, from 6 in 2011 to 200 in 2021 (3.9% of total CPC vs 11%, p<0.001). While total CPC increased constantly during the entire period (APC of 21.7 from 2011 to 2021 in a 0-joinpoint model), CPC for SA increased significantly from 2011 to 2016, were approximately stable from 2016 to 2020 and then had a peak in 2021, after COVID-19 pandemic (APC from 2011 to 2016 of 64.1, APC of 1.2 from 2016 to 2020, APC of 230 after 2020 in a 2-joinpoints model). Total CPC in ED, as well as evaluation for SA and SI increased significantly during the last decade. CPC for SA had an additional increase after COVID-19 pandemic. This picture warrants timely and efficient improvements of emergency settings and mental health resources.